Dose Optimization of the Quinine-phenobarbital Co-administration in Cerebral Malaria Patients: A Physiologically-based Pharmacokinetic Modeling Approach - Teerachat Sae-Heng; Rajith Kumar Reddy Rajoli; Marco Siccardi; Kesara Na-Bangchang (Novel Aspects on Pharmaceutical Research Vol. 5, 2023)
The goal of the study was to forecast the potential quinine dosage regimens when given along with phenobarbital to adult patients with cerebral malaria and complications (such as lactic acidosis and acute renal failure) and concurrent with seizures and acute renal failure who carry wild-type and polymorphic CYP2C19. Cerebral malaria is the most serious consequence of Plasmodium falciparum infection. Cerebral malaria patients with polymorphic CYP2C19 genotypes who receive concurrent treatment with quinine are at risk of inadequate or toxic therapeutic drug concentrations due to metabolic drug interactions. Using Simbiology®, whole-body physiologically-based pharmacokinetic (PBPK) models for quinine, phenobarbital, and quinine-phenobarbital co-administration were built based on previously published data. For model validation, four published articles were utilized. One hundred virtual patients were simulated based on the 14-day and 3-day courses of treatment using the drug-drug interaction approach. The projected results closely matched the observed values (15%). 444When given along with quinine, standard phenobarbital dosage is acceptable for all groups experiencing intermittent or ongoing seizures, regardless of CYP2C19 genotype, renal failure, or lactic acidosis. The area under the curve ratio (AUCR) dose adjustment method produced inaccurate quinine concentrations. According to the PBPK model, quinine should be given to all groups is a loading dose of 2,000 mg IV infusion rate 250 mg/h, followed by 1,200 mg IV rate 150 mg/h. The PBPK models that have been co4444nstructed are reliable for future simulations. Genotyping may not be necessary because the anticipated quinine doses in all groups were comparable regardless of the CYP2C19 genotype.